An empirical analysis on reliability of HRIS data at Petronas Chemicals Group Berhad (PCGB) / Dayang Amanina Syafiqah Abdul Aziz - Abdul Aziz, Dayang Amanina Syafiqah (Faculty of Business and Management, 2013)
A few decades ago, human resources not represent the company much, because people at that time not realize the important of having human resource in the company until now the human resource become the most important key in the successful company. Without human resource management, the company can face the unstable population in the company and it can lead to the surplus or shortage of employee in the company. At PETRONAS Chemicals Group , the company uses a system to collect and process all the data which will serves as the basis for other HRIS data be updated at the same time the system is the avenue whereby organizational hierarchy and positions are updated or maintained in order to support business objectives. HRIS or human resource information system is one of system that using by the organization to smooth the function of the organization it also plays the big role especially in organization. The primary focus of an HRIS is to assist an employee to achieve the organization goals and objective. In this research study, the objective of having this research is to identify the common practice of that lead to effectiveness of HRIS, to examine the level of effectiveness of HRIS and also to identify the relationship between common practices and the level of HRIS effectiveness. The population for this research will be focus on the planner in the PETRONAS Chemicals Group Berhad (PCGB) itself. There a basically 20 of planners in each of company branch. In order to increase the reliability of data an employee and HRIS team need to realize of that their validation and protection of data highly important when managing specified and partly confidential information. The availability of management and validity of data make the HRIS a truly significant and useful tool for overall human resource management and development work.